2021
DOI: 10.24002/ijieem.v3i2.5546
|View full text |Cite
|
Sign up to set email alerts
|

Extended Theory of Planned Behavior (TPB) to Analyze the Batik Purchase Intention of Indonesian Millennials and Gen Z

Abstract: As the nation’s cultural heritage of Indonesia, batik has an important role in the Indonesian economy. This industry provides job opportunities that involve a lot of human resources in it and contributes to the country's foreign exchange through the export of national batik to big countries. Although the development of the batik industry has increased, there are still problems in marketing batik products in Indonesia. These problems can lead to more serious problems such as batik craftsmen leaving the business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Different theoretical models have been used in studies on sustainable consumption behaviour. In sustainable cosmetics studies, the most commonly used theory is the theory of planned behaviour [15,[34][35][36][37], but others include stimulus organism response (SOR) theory [38], norm activation theory [39] and social impact theory [40]. In this study, social dilemma theory was used to better understand the drivers and barriers to consumers' intention to purchase refillable cosmetic products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different theoretical models have been used in studies on sustainable consumption behaviour. In sustainable cosmetics studies, the most commonly used theory is the theory of planned behaviour [15,[34][35][36][37], but others include stimulus organism response (SOR) theory [38], norm activation theory [39] and social impact theory [40]. In this study, social dilemma theory was used to better understand the drivers and barriers to consumers' intention to purchase refillable cosmetic products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the previous statement, TPB is a theory that explains how consumer behavior in the intention to buy a product is influenced by subjective norms, attitude, and perceived behavior control (PBC). Furthermore, Putri & Akbari (2021) have extended TPB to include a brand image on the intention to buy batik, and Gungaphul et al (2022) found empirical evidence that brand image also influences purchase intention.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%